Impact of Digital Panoramic Radiograph Magnification on Vertical Measurement Accuracy. (19th October 2015) - El Hage, Marc; Bernard, Jean-Pierre; Combescure, Christophe; Vazquez, Lydia
Abstract : Objectives. The purpose of this panoramic radiography study was to assess the impact of image magnification on the accuracy of vertical measurements in the posterior mandible. Methods. Six dental implants, inserted in the posterior segments of a resin model, were used as reference objects. Two observers performed implant length measurements using a proprietary viewer with two preset image magnifications: the low (1.9 : 1) and the medium (3.4 : 1) image magnifications. They also measured the implant lengths in two Digital Imaging Communications in Medicine viewers set at low (1.9 : 1), medium (3.4 : 1), and high (10 : 1) image magnifications. Results. The error between the measured length and the real implant length was close to zero for all three viewers and image magnifications. The percentage of measurements equal to the real implant length was the highest (83.3%) for the high image magnification and below 30% for all viewers with the low image magnification. Conclusions. The high and medium image magnifications used in this study allowed accurate vertical measurements, with all three imaging programs, in the posterior segments of a mandibular model. This study suggests that a low image magnification should not be used for vertical measurements on digital panoramic radiographs when planning an implant in the posterior mandible.